THU0609 Patient-Reported Outcomes from A Phase 3 Study of Baricitinib versus Placebo or Adalimumab in Patients with Active Rheumatoid Arthritis and An Inadequate Response To Background Methotrexate Therapy. (15th July 2016) - Keystone, E.; Taylor, P.; Tanaka, Y.; Gaich, C.; DeLozier, A.M.; Dudek, A.; Velasco Zamora, J.; Covarrubias Cobos, J.; de Bono, S.; Arora, V.; Yang, L.; Linetzky, B.; et al.
Abstract : Background: Baricitinib (bari), an oral JAK1 and JAK2 inhibitor, was efficacious in a Ph 3 study (RA-BEAM) in RA patients (pts) with active disease and an inadequate response (IR) to MTX. 1 Objectives: To evaluate patient-reported outcomes (PROs) from RA-BEAM. Methods: Pts on stable background MTX were randomized to placebo (PBO), bari 4 mg QD, or adalimumab (ADA) 40 mg Q2W. PROs listed in the table and the Work Productivity and Activity Impairment-Rheumatoid Arthritis (WPAI-RA) were collected on electronic tablets during study visits. Bari vs. PBO and bari vs. ADA were assessed with ANCOVA and logistic regression models. Results: 1305 pts were randomized. Functional disability at baseline (mean HAQ-DI) was: 1.55, 1.57, 1.59 for PBO, bari, and ADA, respectively. Compared to PBO, bari was superior in physical function, Pt's Global Assessment of Disease Activity (PtGDA), pain, fatigue and quality of life (physical component score [PCS]), at Wk 12 and 24. Compared to ADA, bari was superior in physical function, PtGDA, and pain at Wks 12, 24 and 52. Compared to PBO, a similar proportion of bari and ADA pts were employed throughout the study. Statistically significant improvements in all components of the WPAI-RA (absenteeism, presenteeism, work productivity loss and activity impairment) were seen in the bari pts compared to PBO at Wk 12; statistically significant improvements were seen for work loss and activity impairment for bari pts compared to ADA at Wk 12. Conclusions: In this Ph 3 study of RA patients with an IR to MTX, treatment with bari resulted in significant improvement in most PROs compared with PBO or ADA, including functional disability, pain, and fatigue. References: Taylor et al. Arthritis Rheumatol 2015;67(S10) Disclosure of Interest: E. Keystone Consultant for: Abbott Laboratories, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, F. Hoffmann-La Roche Inc, Genentech Inc, Janssen Inc, Eli Lilly and Company, Merck, Pfizer Pharmaceuticals, UCB, P. Taylor Consultant for: Eli Lilly & Company, UCB, Pfizer, Galapagos, AbbVie, Takeda, Bristol-Myers Squibb, Y. Tanaka Consultant for: Eli Lilly & Company, AbbVie, Daiichi-Sankyo, Chugai, Takeda, Mitsubishi-Tanabe, Bristol-Myers Squibb, Astellas, Eisai, Janssen, Pfizer, Asahi-kasei, GlaxoSmithKline, UCB, Teijin, MSD, Santen, Taisho-Toyoma, Kyowa-Kirin, C. Gaich Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, A. DeLozier Employee of: Eli Lilly and Company, A. Dudek Consultant for: Eli Lilly and Company, J. Velasco Zamora Consultant for: Eli Lilly and Company, J. Covarrubias Cobos Consultant for: Eli Lilly and Company, S. de Bono Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, V. Arora Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, L. Yang Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, B. Linetzky Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, M. Weinblatt Consultant for: Eli Lilly & Company, AbbVie, Pfizer, Crescendo Bioscience